Gesture phenomenon: From Ontological-Conceptual Status to Aesthetic Category - Voronovskaya, Olga (Journal of History Culture and Art Research, 2020)
The purpose of the study is to cover the phenomenon of gesture in a wide range of its consideration as the inseparable integrity of the content and form of the subject, which is expressed in a space-time dimension; identifying patterns of gesture existence in various aspects of human life and in art; comprehending the gesture as an aesthetic category that embraces both the different types of art and the branches outside of it - psychology, philosophy, aesthetics. The research methodology is based on a complex approach, which makes it possible to consider the phenomenon of gesture as a "fragment object" of scientific reality in a wide range. The scientific novelty of the research lays in referring to the gesture as a semiotic object that has three semiotic functions: semantic, syntactic, and pragmatic. It was concluded in the study that gesture, as a fact of culture, acts simultaneously as a phenomenon of culture, which reveals itself not only as a sphere of gesture display but also as an environment of its existence and functioning. Today the study of gesture in art has evolved into a particular area of science with rich traditions and numerous scientific schools where the gesture is considered as a component of an integrated language system and as an important component in the creation and perception of art.